Reconstruction of Hyper‐Thermostable Ancestral L‐Amino Acid Oxidase to Perform Deracemization to D‐Amino Acids. Issue 24 (2nd November 2021) - Ishida, Chiharu; Miyata, Ryo; Hasebe, Fumihito; Miyata, Azusa; Kumazawa, Shigenori; Ito, Sohei; Nakano, Shogo
Abstract: L‐amino acid oxidases (LAAOs) with broad substrate specificity can be used in the deracemization of D, L‐amino acids (D, L‐AAs) to their D‐enantiomers. Hyper‐thermostable LAAO (HTAncLAAO) was designed through a combination of manual sequence data mining and ancestral sequence reconstruction. Soluble expression of HTAncLAAO (>50 mg/L) can be achieved using an E. coli system. HTAncLAAO, which recognizes seven L‐AAs as substrates, exhibits extremely high thermal stability and long‐term stability; the t1/2 value was 95 °C and <5% activity loss after incubation of the enzyme at 30 °C for 1 week. Deracemization could be achieved at 40 °C with a small amount of enzymes compared to previously reported LAAOs. A total of 0.4 mg (2 U) of HTAncLAAO is enough to deracemize three D, L‐AAs at a preparative scale with high enantiomeric excess (>99 % ee, D‐enantiomer). These results suggest that HTAncLAAO is an excellent biocatalyst to perform this deracemization. Abstract : BioCATalysis : The hyper‐thermostable ancestral L‐amino acid oxidase (HTAncLAAO), which was screened from a sequence database, converted L‐amino acids to D‐enantiomers at high temperatures using a one‐pot reaction. HTAncLAAO had the highest thermo‐ and long‐term stability compared to previously reported LAAOs. HTAncLAAO is a useful biocatalyst in the deracemization to D‐amino acids.